Immunotherapy for neuroblastoma by hematopoietic cell transplantation and post-transplant immunomodulation. (May 2023) - Ash, Shifra; Askenasy, Nadir
Abstract: Neuroblastoma represents a relatively common childhood tumor that imposes therapeutic difficulties. High risk neuroblastoma patients have poor prognosis, display limited response to radiochemotherapy and may be treated by hematopoietic cell transplantation. Allogeneic and haploidentical transplants have the distinct advantage of reinstitution of immune surveillance, reinforced by antigenic barriers. The key factors favorable to ignition of potent anti-tumor reactions are transition to adaptive immunity, recovery from lymphopenia and removal of inhibitory signals that inactivate immune cells at the local and systemic levels. Post-transplant immunomodulation may further foster anti-tumor reactivity, with positive but transient impact of infusions of lymphocytes and natural killer cells both from the donor, the recipient or third party. The most promising approaches include introduction of antigen-presenting cells in early post-transplant stages and neutralization of inhibitory signals. Further studies will likely shed light on the nature and actions of suppressor factors within tumor stroma and at the systemic level. Graphical Abstract: ga1 Highlights: Neuroblastoma is an immunogenic tumor. Neuroblastoma is treatable by allogeneic and haploidentical bone marrow transplantation. Graft versus tumor reactions are mediated by the lymphoid progeny of hematopoietic progenitors, which are tolerant to the host. Effective graft versus tumor reactivity requires post-transplant immunomodulation. Boost of anti-tumor immunity may be attained by administration of dendritic cells. ∼Effective immunotherapy to neuroblastoma should consider annulation of tumor-derived suppressor-mechanisms.